Reconciling Oxygen and Aerosol Delivery with a Hood on In Vitro Infant and Paediatric Models - Shu-Hsin Chen; Hsiu-Chu Chang; Ming-Yi Chien; Jinxiang Xi; Hui-Ling Lin (MDPI AG, 2021)
This study aimed to evaluate optimal aerosol and oxygen delivery with a hood on an infant model and a paediatric model. A facemask and a hood with three inlets, with or without a front cover, were used. A small-volume nebuliser with a unit-dose of salbutamol was used for drug delivery and an air entrainment nebuliser was used to deliver oxygen at 35%. Infant and paediatric breathing patterns were mimicked; a bacterial filter was connected to the end of a manikin trachea for aerosol drug collection, and an oxygen analyser was used to measure the oxygen concentration. For the infant model, inhaled drug dose was significantly higher when the nebuliser was placed in the back of the hood and with a front cover. This was verified by complementary computational simulations in a comparable infant-hood model. For the paediatric model, the inhaled dose was greater with a facemask than with a hood. Oxygen delivery with a facemask and a hood with a front cover achieved a set concentration in both models, yet a hood without a front cover delivered oxygen at far lower concentrations than the set concentration.